Creative environments for design education and practice: A typology of creative spaces. (May 2018) - Thoring, Katja; Desmet, Pieter; Badke-Schaub, Petra
Abstract : This article presents a typology of creative spaces that is relevant to facilitating creative working and learning processes for designers. Drawing on qualitative user research with cultural probes in a design thinking institution, this typology identifies five different types of creative spaces along with five related spatial qualities. The paper suggests characteristics and criteria for each type and quality and summarizes the results in a framework. A second study in a practitioner's context validated these findings. The work presented in this article contributes to a better understanding of the impact of the built environment for creative design in education and practice and might inspire designers and educators to improve the design of their work environments. Highlights: Currently, there exists no comprehensive typology of creative spaces. Five space types and five qualities emerged from grounded theory and a case study. To facilitate creative design processes, all five space types should be present. Five qualities determine whether a space is perceived as positive or negative.